Understanding The Influx Of Indonesian Immigrants In Rural Johor: Aspirations And Strategies - Ngah, Ibrahim; Meeteren, Masja van (Universiti Sains Malaysia, 2016)

(untitled)
The rapid pace of development in Malaysia in recent decades has caused an acute labour shortage in the rural sector due to continuous out-migration of young rural people to urban areas which was overcome by the immigration of foreign labourers from neighbouring countries, particularly from Indonesia. This study aims to investigate immigrants’ aspirations and their behavior to achieve their migration goals. The characteristics of immigrants and migration history are also examine in relation to the aspirations and intention to stay in Malaysia or return to home country. The study reveals that out of 383 respondents only 25 wished to stay permanently. Some of the immigrants’ characteristics, aspirations and strategies vary with the intention to return and to stay in Malaysia permanently. Immigrants who aspired to return prioritize their responsibilities to their country of origin’s socioeconomic development. Therefore, their efforts to reach the migration goals are based on saving money for investment in their origin country. The main purpose of their migration to Malaysia was shortterm financial gain with the objective of setting up a business or investment in economic activities on returning to their homeland. Immigrants who have the intention to stay in Malaysia permanently tended to put more efforts in investing in a strategy that involves adapting to life in the host country. They regard it a good strategy to maintain close relationships with local people.